Nos nervos, na carne, na pele : uma etnografia sobre prostituição travesti e o modelo preventivo de AIDS - Silva, Larissa Maués Pelúcio (Universidade Federal de São Carlos, 2007)
This dissertation looks at the discussion that unfolds within the official STD/AIDS prevention model set up to provide attention to travestis involved in prostitution in the city of São Paulo. Using ethnographic methods, I have attempted to investigate how preventive discourse circulates through the travesti universe and what logic presides over the process, from the point of view of the particular ethos of this clientele. The concerns within the field have turned toward how AIDS is signified by travestis, the meanings of illness and suffering, as well as the care that is given to the body and thereby, to the construction of personhood. The project Tudo de Bom!, housed within the public health organ STD/AIDS City of São Paulo which belongs to the Municipal Secretariat of Health, provided empirical bases for my study of how the preventive model was operationalized. My point of departure is the notion that the adopted preventive model - notwithstanding the specific and differentiated connotation it is given in the case of particular segments - can be characterized by a scientific and technical rationality and universalizing normative values that are not necessarily compatible with the social logic that prevails in the organization of the pertinent social networks and the differentiated values upon which they are based. I go on to suggest the hypothesis that recent public policies devoted to this segment have focused their attention on bearers of deviant sexualities as a target population - among which travestis are included - without any greater consideration of the relationship of the latter to the men with whom they relate sexually. Since these men fall within normalized categories, they become invisible for hetero-centered health policies that choose their target groups through criteria based on epidemiological references rather than considering the social and cultural dimensions of relationships in the different contexts in which these populations act.
Keywords: Antropologia; Antropologia da saúde; Travestis; AIDS (Doença); Gênero; Travestis [transvestites]; AIDS prevention model; Sexuality; Gender and health; CIENCIAS HUMANAS::ANTROPOLOGIA